Syi’ah Imamiyah dan Perkembangan Hukum Islam - Marlian Arif Nasution (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2021)
Abstract. Syi'ah in the history of Islamic thought is a stream that emerged due to politics and subsequently developed into a stream of theology. Since the death of the Prophet and the interruption of revelation, problems have continued to arise in the lives of the companions, especially in matters of law. Islamic law is a logical reflection of the struggles of various actual situations which have resulted in works of figh. That way, the character of fiqh that was born was to meet the needs of the people of his time. The method used in this paper is qualitative-descriptive, namely elaborating works on the development of Shi'ah in the Islamic world to answer the objectives of this paper. In the field of legal thought, the Shi'ites have their own Usul Fiqh and istinbat principles which differ greatly from those of the existing Sunni schools of thought. This Shi'a school consists of several groups which have different beliefs. So that in the field of proposal they reject all grounds that are not in accordance with their mazhab. The Shi'ah Imamiyah consists of twelve imams who become their marja '(role models) in matters relating to matters of religious teachings. Generally, the Shi'ah Imamiyah circles have their own basis for performing legal istinbat, namely based on the Al-Kitab, Al-Sunnah, Al-Ijma 'and Al-Aql.Keywords: Syi’ah, Islamic Law